Agrisilviculture management and productivity system in Timusu village, Liliriaja district, Soppeng Regency. Issue 1 (October 2020) - Firdausi, F; Umar, A; Bachtiar, B; Larekeng, S H
Abstract: Agroforestry can become one of the solutions in the land management system to overcome problems arising from the land-use change. The study purposes were to know the technical form of agrisilviculture management system and to know the productivity of the agrisilviculture system. Data of agrisilviculture management systems were obtained from observation results, interviews, questionnaires, and literature study, which then being analyzed descriptively with a qualitative approach. This study was conducted in Timusu Village, Liliriaja District, in Soppeng Regency. In total, 15 farmers were selected as respondents. Data on the productivity of agriculture systems were obtained from interviews and vegetation surveys. The land area classified into three categories, such as the land area less than 0.6 Ha, 0.6 to 1 Ha, and more than 1 Ha. The data were analyzed quantitatively. The results showed that the agrisilviculture management system in Timusu Village consists of land preparation, seedling procurement, planting, maintenance, and harvesting. The average amount of agrisilviculture productivity in the land area classification of more than 1 Ha was equal to Rp 23.167.389/Ha/year, the land classification of 0.6 to 1 Ha was Rp15.333.366/Ha/year, and land area classification of less than 0.6 was Rp18.455.483/Ha/year